Measured versus reported parental height. Issue 9 (19th August 2005) - Cizmecioglu, F; Doherty, A; Paterson, W F; Young, D; Donaldson, M D C
Abstract : Background: Parental height data are essential in the assessment of linear growth in children. A number of studies have documented inaccuracy in self-reported adult height. Aims: To determine whether there is a tendency for men to overestimate and women to underestimate their height. Methods: Heights of parents of children attending outpatient clinics were measured (MHt) and compared with reported heights (RHt). Results: Two hundred parents (100 males; 100 females), mean (range) age 37.8 (20.8–69.3) years, were measured. Males overestimated height, with mean (SD) RHt–MHt 1.09 (1.96) cm, while females reported height relatively accurately, with RHt–MHt −0.09 (2.37) cm. Conclusions: The hypothesis that males overestimate height is confirmed. While the hypothesis that women underestimate is not supported, we recommend accurate measurement of both parents, given the considerable degree of individual variation in RHt−MHt for both sexes.